THE IMPACT OF TASTE AND LOCATION ON CUSTOMER LOYALTY: A STUDY OF SUPER PENYET 268 IN PEKANBARU CITY - Darimi, Darimi (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to evaluate the impact of taste and location on customer loyalty at Super Penyet 268 in Pekanbaru City. Using a quantitative approach, data were collected from 100 customers who had made at least three purchases. The analysis, conducted via multiple linear regression, revealed that both taste and location significantly and positively affect customer loyalty. This finding underscores the importance of delivering a consistent taste experience and maintaining a strategic, accessible location to encourage customer loyalty. Based on the study results, Super Penyet 268 is advised to enhance product variety, ensure hygienic food preparation, and improve aspects of the physical location, such as parking security and organization, to reinforce customer loyalty.